Ὁ Θεὸς ἔρως ἐστί: Origen and the Attribution of ἔρως to God. - Tolan, Daniel J. (International Journal of the Platonic Tradition, 2024)
Origen of Alexandria uses the language of ἔρως to explain God's desire to be with humanity. However, Plato's classic definition of ἔρως as a mix of poverty and plenty seems to be at odds with Origen's commitment to classical theism. This article explains why Origen does not consider this attribution to contradict his theological commitments. It starts with a discussion of Origen's theory of divine attributes, the ἐπίνοιαι Χριστοῦ. Next, Origen's doctrine of passio caritatis , which states that God can actively will to be passive, is explained. Then, Origen's familiarity with Plato's Symposium is demonstrated. The article then considers Origen's attribution of ἔρως to God, and its context, in the Commentarium in Canticum Canticorum ; it emerges that the Incarnation is, for Origen, God's most erotic act. The final section shows that Origen maintains his understanding of God's erotic, incarnational movement towards fallen humanity in works other than the Commentarium in Canticum Canticorum.